Straightforward Generation of Pillared, Microporous Graphene Frameworks for Use in Supercapacitors. (28th September 2015) - Yuan, Kai; Xu, Yazhou; Uihlein, Johannes; Brunklaus, Gunther; Shi, Lei; Heiderhoff, Ralf; Que, Mingming; Forster, Michael; Chassé, Thomas; Pichler, Thomas; Riedl, Thomas; Chen, Yiwang; et al.
Abstract : Microporous, pillared graphene‐based frameworks are generated in a simple functionalization/coupling procedure starting from reduced graphene oxide. They are used for the fabrication of high‐performance supercapacitor devices.